HUBUNGAN KELENTUKAN PERGELANGAN TANGAN PADA AKURASI SERVIS BACKHAND TOPSPIN TENIS MEJA PADA EKSTRAKURIKULER PUTRA SMP SWASTA SANTO YOSEF DURI - Trifena Andrianta Kacaribu; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the correlation of wristflexing with the accuracy of the backhand topspin table tennis service on the male extracurricular Santo Yosef Duri Junior High School. This type of research conducted in this study uses a correlational research design. The population in this study were 20 people, with saturated sampling technique. Saturated sampling is a sampling technique when all members of the population are used as samples. From the results obtained wrist flexion there is a relationship with the accuracy of the backhand topspin service in the table tennis game on the male extracurricular of St. Joseph's Private Junior High School, namely the acquisition of rcount (0.963)> from the acquisition of rtable (0.456) atα = 0.05. There is a relationship of wrist flexion to the accuracy of the backhandtopspin table tennis extracurricular services of the Santo Yosef Duri Rhitung Private Junior High School (0.963)> from the acquisition of Rtabel (0.456) at α = 0.05.Key Words: Wrist Flexion, Topspin Backhand Service Accuracy